Manajemen Strategi Pengelolaan Ekowisata Mangrove Untuk Meningkatkan Perekonomian Masyarakat: Studi Kasus Mangrove Gunung Anyar Kota Surabaya - Fikri Akbar Syarifuddin; Meirinawati M; Eva Hany Fanida; Fitrotun Niswah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Gunung Anyar Mangrove Ecotourism is a conservation-based tourist destination with significant potential to support environmental preservation while improving the local community’s economy through the empowerment of Micro, Small, and Medium Enterprises (MSMEs). However, its management continues to face several challenges, including a low number of tourist visits, limited accessibility to the site, and the suboptimal management of tourism facilities and promotional activities. This study aims to analyze the strategic management of Gunung Anyar Mangrove Ecotourism in improving the local community’s economy based on the Ministry of Tourism’s destination development indicators, namely accessibility, amenities, attractions, and promotion. This study employed a qualitative research method with a case study approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the accessibility aspect is still constrained by limited transportation options and inadequate directional signage leading to the tourist destination. Regarding amenities, the management has provided various supporting facilities for visitors and MSME operators, although infrastructure maintenance requires further improvement. The attraction aspect has been developed through mangrove ecotourism activities, environmental conservation programs, and community-based economic activities. Meanwhile, promotion has been conducted through digital platforms and social media; however, these efforts have not yet succeeded in significantly increasing tourist arrivals.